Does Using Multiple Computer Monitors for Office Tasks Affect User Experience? : A Systematic Review. - Gallagher, Kaitlin M.; Cameron, Laura; De Carvalho, Diana; Boulé, Madison (Human Factors, 2021)
Objective: To compare the impact of multiple computer monitor configurations on health and performance outcomes compared to the use of a single monitor.Background: Multiple monitor configurations are used in office settings to promote increased productivity by providing more screen space; however, it is unknown if there are health-related trade-offs to increased productivity.Method: A systematic review was conducted according to the PRISMA statement guidelines and adapted the best evidence synthesis.Results: Eighteen studies were included in our review. There was strong evidence that implementing dual monitors is in line with users' preference. There was also moderate evidence for controlled laboratory studies demonstrating that multiple monitors may increase task efficiency with decreased desktop interaction; however, implementing multiple monitors may also result in nonneutral neck postures for users.Conclusion: More research needs to be conducted on biomechanical exposures when using larger displays. Longitudinal field studies should be conducted to determine the influence of monitor interventions on health, productivity, and well-being. All studies must consider task complexity and user positioning and should measure health and productivity outcomes together. Researchers must also consider up-to-date purchasing trends when choosing the monitor configurations and sizes for their studies.Application: Regulatory bodies and practitioners can use the results to develop evidence-based monitor guidelines and inform decision-making in practice, respectively. Researchers can use this information to design future studies on monitor configurations that incorporate current purchasing trends.